2018
DOI: 10.1186/s13148-018-0548-2
|View full text |Cite
|
Sign up to set email alerts
|

CDX2 in colorectal cancer is an independent prognostic factor and regulated by promoter methylation and histone deacetylation in tumors of the serrated pathway

Abstract: BackgroundIn colorectal cancer, CDX2 expression is lost in approximately 20% of cases and associated with poor outcome. Here, we aim to validate the clinical impact of CDX2 and investigate the role of promoter methylation and histone deacetylation in CDX2 repression and restoration.MethodsCDX2 immunohistochemistry was performed on multi-punch tissue microarrays (n = 637 patients). Promoter methylation and protein expression investigated on 11 colorectal cancer cell lines identified two CDX2 low expressors (SW6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 32 publications
9
42
0
Order By: Relevance
“…With regard to CDX2 expression, it should be noted that the CDX2‐negative tumors represent a larger fraction in this cohort compared with the original Dalerba et al cohort . Our results are in concordance with recent studies that exhibited higher expression rates of CDX2 absence/loss in stage II tumors . Nevertheless, our results confirm the role of CDX2 expression as a prognostic factor, as has been previously demonstrated, and also display its correlation to tumor location.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to CDX2 expression, it should be noted that the CDX2‐negative tumors represent a larger fraction in this cohort compared with the original Dalerba et al cohort . Our results are in concordance with recent studies that exhibited higher expression rates of CDX2 absence/loss in stage II tumors . Nevertheless, our results confirm the role of CDX2 expression as a prognostic factor, as has been previously demonstrated, and also display its correlation to tumor location.…”
Section: Discussionsupporting
confidence: 93%
“…According to the CCLE data, however, CDX2 copy number is poorly correlated with gene expression, and furthermore, in a real patient dataset (TCGA), mRNA expression was not significantly different between patients harboring a gain or amplification of chr13q12.2. However, as a recent study described that CDX2 loss through demethylation and HDAC inhibition is an adverse prognostic factor and linked to molecular features of the serrated pathway [68], CDX2 may act as an oncogene in tumors with a high expression of CDX2, but this is not necessarily applicable to all cases of CRC with chr13q12.2 aberration.…”
Section: Discussionmentioning
confidence: 99%
“…Our current studies also highlights the detailed mechanism of Wnt/β-catenin pathway regulated by JARID1B in CRC cells. Caudal-type homeobox transcription factor 2 (CDX2), an essential intestinespecific regulator, is involved in the development and differentiation of intestinal epithelial cells and regulates the balance between cell proliferation and differentiation [33]. In the present study, many studies revealed that CDX2 expression level was associated with CRC cells proliferation and poor prognosis for patients with CRC [34].…”
Section: Discussionmentioning
confidence: 60%